Development of BDD models for decision support in phased mission systems - Zhang, Yang (2016)
Autonomous systems are becoming increasingly commonplace, with applications either existing or suggested in many different industries. As levels of autonomy increase, the need for these systems to interpret with environments in which they operating and make decisions about their own future actions following internal failures or external threats. In the past, reliability analysis methods have been suggested as having the potential to provide information that could be used in a real-time decision support tool for autonomous systems in changing environments. Real-time support is particularly important in systems such as unmanned aerial vehicles (UAV), where any delay in making a decision following a failure occurrence or the emergence of a threat could be catastrophic.